Mineralogy and Pore Structure of Marine–Continental Transitional Shale: A Case Study of the Upper Carboniferous Keluke Formation in the Eastern Qaidam Basin, China - Guo, Yingchun; Fang, Xinxin; Wang, Haifeng; Wang, Na (Frontiers in Earth Science, 2022)
Organic-rich shale and associated fine-grained sedimentary rocks of marine-continental transitional facies were well developed in the Upper Carboniferous Keluke Formation in the Eastern Qaidam Basin, which is expected to be a set of potential shale gas exploration and development target. Mineralogy and pore structure of marine-continental transitional shale were investigated systematically based on thin-section identification, X-ray diffraction (XRD), helium porosity test and pressure-pulse permeability measurement, scanning electron microscopy (QEMSCAN), field emission scanning electron microscopy (FESEM), and high-pressure mercury injection (MICP) and nitrogen adsorption. Thin section, XRD, and QEMSCAN data suggest that marine–continental transitional shale has complex mineral compositions, resulting in mixed rocks and mixed sequences. FE-SEM images show that interparticle and intercrystalline pores are popular in the Keluke Shales, with minor dissolution pores and microfractures. No secondary organic matter pores occur in the Keluke Shales because organic macerals are dominated by vitrinite and inertinite, where only primary pores can be found among organic matter frameworks. MICP and nitrogen adsorption indicate that pore size distributions follow a bimodal pattern and proportions of micro-scale pores and macro-scale pores increase in an order: bioclastic limestone, argillaceous bioclastic limestone, silty mudstone, argillaceous siltstone. The differences in pore structure are caused by sedimentary facies and associated mineralogy and diagenesis. This study can provide a crucial theoretical guidance for sweet spots determination and deep understanding of transitional shale gas potential.